Attenuation of Seizures, Cognitive Deficits, and Brain Histopathology by Phytochemicals of (Poaceae) in Acute and Chronic Mutant Epilepsy Models - Fred Ssempijja MSc, PhD Fellow; Samuel Sunday Dare MSc, PhD Fellow; Edmund E. M. Bukenya PhD; Keneth Iceland Kasozi MSc, PhD Fellow; Ritah Kenganzi BSc; Edgar Mario Fernandez MSc, MMed; Marta Vicente-Crespo PhD (SAGE Publishing, 2023)
Imperata cylindrica is a globally distributed plant known for its antiepileptic attributes, but there is a scarcity of robust evidence for its efficacy. The study investigated neuroprotective attributes of Imperata cylindrica root extract on neuropathological features of epilepsy in a Drosophila melanogaster mutant model of epilepsy. It was conducted on 10-day-old (at the initiation of study) male post-eclosion bang-senseless paralytic Drosophila ( para bss1 ) involved acute (1-3 h) and chronic (6-18 days) experiments; n = 50 flies per group (convulsions tests); n = 100 flies per group (learning/memory tests and histological examination). Administrations were done in 1 g standard fly food, per os. The mutant flies of study ( para bss1 ) showed marked age-dependent progressive brain neurodegeneration and axonal degeneration, significant (P < 0.05) bang sensitivity and convulsions, and cognitive deficits due to up-regulation of the paralytic gene in our mutants. The neuropathological findings were significantly (P < 0.05) alleviated in dose and duration-dependent fashions to near normal/normal after acute and chronic treatment with extract similar to sodium valproate. Therefore, para is expressed in neurons of brain tissues in our mutant flies to bring about epilepsy phenotypes and behaviors of the current juvenile and old-adult mutant D. melanogaster models of epilepsy. The herb exerts neuroprotection by anticonvulsant and antiepileptogenic mechanisms in mutant D. melanogaster due to plant flavonoids, polyphenols, and chromones ( 1 and 2 ) which exert antioxidative and receptor or voltage-gated sodium ion channels' inhibitory properties, and thus causing reduced inflammation and apoptosis, increased tissue repair, and improved cell biology in the brain of mutant flies. The methanol root extract provides anticonvulsant and antiepileptogenic medicinal values which protect epileptic D. melanogaster . Therefore, the herb should be advanced for more experimental and clinical studies to confirm its efficacy in treating epilepsy.